Canva's Optimization in Improving the Learning Quality of Elementary School Students in Grade 5 Indonesian Language Subjects (Descriptive Study at SDN 3 Munjuljaya Purwakarta) - Nia Kaniati; A. Hafidz Munandar; Agus Virgo; Waska Warta (Civiliza Publishing, Indonesia., 2025)
Digital transformation in education requires teachers to be able to integrate technology as part of a meaningful learning process. One of the main challenges at the elementary school level is the limited use of digital media that is interactive and in accordance with the characteristics of students' development, especially in Indonesian language learning. Canva as a digital design platform has great potential to improve the quality of learning through visualisation of engaging, interactive, and contextual materials. However, in practice, the use of Canva in elementary schools is often not optimally optimized and tends to be limited to simple presentation functions. This study aims to describe and analyze the optimization of the use of Canva in improving the quality of Indonesian learning in grade V students at SDN 3 Munjuljaya Purwakarta. This study uses a qualitative approach with a descriptive method. Data collection was done through learning observations, in-depth interviews with teachers and students, and documentation studies of Canva-based learning tools and media. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing by testing the validity of the data using triangulation of sources and techniques. The results show that Canva's optimization makes a positive contribution to the quality of Indonesian learning. Canva is used by teachers in the planning, implementation, and evaluation stages of learning through the preparation of visual media, infographics, and interactive teaching materials. Using Canva can increase student engagement, clarify material understanding, and create a more engaging and enjoyable learning atmosphere. However, Canva's optimization still faces obstacles in the form of limited mastery of technology by some teachers and limited support facilities. The conclusion of this study shows that Canva is effectively used as an Indonesian learning medium in elementary schools if it is optimized in a planned and sustainable manner. These findings provide practical implications for teachers and schools in developing technology-based learning that is creative and relevant to student needs.